Pengaruh Media Pembelajaran YouTube terhadap Hasil Menulis Paguneman Pada Siswa Kelas VII SMP Negeri 1 Ciniru - Nur Aripin; Leni Nuraeni (Jurnal Studi Guru dan Pembelajaran, 2025)
This study aims to determine the effect of YouTube learning media on student learning outcomes in writing paguneman texts in class VII of SMP Negeri 1 Ciniru. The background of this study is based on students' low ability in writing Sundanese dialogues, which is characterized by a lack of understanding of conversational structures and minimal creativity in composing paguneman scripts. This study uses a quantitative approach with an experimental one-group pretest-posttest design method. The research sample consisted of 32 class VII-A students selected through a purposive sampling technique. The instruments used included writing tests (pretest and posttest), observation, and documentation. Data analysis was carried out through normality tests and t-tests (paired sample t-tests). The results showed that there was a significant increase in students' average scores from 56.94 (pretest) to 76.97 (posttest). The t-test results produced a significance value of 0.000 <0.05, which means there was a significant difference between the results before and after treatment. YouTube learning media has been proven to be able to improve students' understanding of the structure, content, and context of dialogues in a more interesting way through audio-visual displays. In addition, this media also increases students' motivation and active participation during the learning process. Thus, the use of YouTube can be used as an alternative strategy in Sundanese language learning, especially in writing paguneman texts, to create a more effective and contextual learning process.